Crisis, Climate Change and Comitology: Policy Dismantling Via the Backdoor?. (16th March 2020) - Burns, Charlotte; Tobin, Paul
Abstract: The EU is reputed to be a climate pioneer. However, the EU has been beset by crises, with potentially negative consequences for climate ambitions. The coding and analysis of EU climate legislation between 1998 and 2015 reveal that while the rate of creating climate policy has increased since the onset of the crisis, the ambition of these policies has waned. Technical policy instruments (comitology) at the EU level, namely delegated and implementing acts (DIA), are analysed alongside the legislation adopted under the ordinary legislative procedure (OLP). If they were applied as indicated in the treaties, the technical DIA measures should not influence the EU's policy ambitions, but in fact, during the crisis era, DIA measures were used more frequently than during the pre‐crisis era, and used in three out of the four cases that weaken policy, suggesting that a minor dismantling of climate policy is taking place at EU level, but via the back door.